EXPEDIENCY USING OF LOW-PROTEIN UKRAINIAN DISHES AND KETO/AMINO ACIDS IN THE TREATMENT OF CHRONIC KIDNEY DISEASE STAGE IV-V - Nykula, T. D.; Moyseyenko, V. O.; Naumova, O. O. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Through the analysis of literature, the results of own research and development, 48-year-old experience in the nephrologìcal clinic outlines the dietary treatment of chronic kidney disease (CKD). Common issues with dietary interventions in CKD, optimal protein diet lowprotein quota must provide, culinary food processing of dietary interventions in patients with CKD. Particular attention is drawn to the use of Ukrainian low-protein dishes, which were developed by the author, and their combination with ketoacids including Ketosteril.